SOCIAL CONTEXT, PARTICIPATION, AND GOAL-ORIENTED COMMUNICATIVE INTERACTION OF SCHOOL AGED CHILDREN WITH MOTOR IMPAIRMENTS WHO USE AUGMENTATIVE AND ALTERNATIVE COMMUNICATION: VOICE AND CHOICE - Batorowicz, Beata (My University, 2015)
This dissertation explores the social context of children with severe motor and communication impairments who use augmentative and alternative communication (AAC), examining how they participate socially, and how they interact in a goal-oriented play activity. Chapter One provides the context by reviewing literature concerning the children who use AAC: describing their presentation, outlining the role of environmental influences, and reviewing what is known about their social context, participation and communicative interactions. This chapter reviews the issues faced by children who use AAC and outlines the thesis purpose and objectives. Chapter Two presents a qualitative study that explores the children’s social context, participation and social relationships from both children’s and parents’ perspectives. This study provides insight into children’s communicative abilities but highlights their limited social context and opportunities and supports for communicative interaction and social participation. Chapter Three presents a study that explores the communicative interaction within goal-oriented play activity. This study found that, if you give children who use AAC a ‘voice’, they experience communicative success. Group differences were evident, however. Compared to their peers, children using AAC were less specific, made more and different errors and received more help from partners. This study provides evidence of how contextual elements within activity settings could be altered so children could actively participate. Chapter Four presents a conceptual framework for understanding social context. This chapter integrates person-focused and environment-focused perspectives and leads to development of a framework that depicts the transactional influences of children and social environments. Recommendations for future studies are presented. Finally, Chapter Five discusses the implications of this dissertation, placing the insights gained from the empirical studies in the context of the proposed framework. Suggestions for further research and interventions are made that may improve health and developmental outcomes in children with severe motor and communication impairments.
SOCIAL CONTEXT OF CHILDREN WHO USE AIDED COMMUNICATION
Keywords: Augmentative and Alternative Communication; Children; Social Context; Environmental Infleunces; Communicative Interaction